Colloidal self-assembly concepts for light management in photovoltaics. Issue 4 (May 2015) - Karg, Matthias; König, Tobias A.F.; Retsch, Markus; Stelling, Christian; Reichstein, Paul M.; Honold, Tobias; Thelakkat, Mukundan; Fery, Andreas
<x xml:space="preserve">Abstract</x> Colloidal particles show interaction with electromagnetic radiation at optical frequencies. At the same time clever colloid design and functionalization concepts allow for versatile particle assembly providing monolayers of macroscopic dimensions. This has led to a significant interest in assembled colloidal structures for light harvesting in photovoltaic devices. In particular thin-film solar cells suffer from weak absorption of incoming photons. Consequently light management using assembled colloidal structures becomes vital for enhancing the efficiency of a given device. This review aims at giving an overview of recent developments in colloid synthesis, functionalization and assembly with a focus on light management structures in photovoltaics. We distinguish between optical effects related to the single particle properties as well as collective optical effects, which originate from the assembled structures. Colloidal templating approaches open yet another dimension for controlling the interaction with light. We focus in this respect on structured electrodes that have received much attention due to their dual functionality as light harvesting systems and conductive electrodes and highlight the impact of inter-particle spacing for templating.